Impact of Musculoskeletal Ultrasound in an Outpatient Rheumatology Clinic. Issue 4 (28th March 2013) - Micu, Mihaela C.; Alcalde, María; Sáenz, José Ignacio; Crespo, Manuel; Collado, Paz; Bolboacă, Sorana D.; Naredo, Esperanza
Abstract Objective To evaluate the impact of musculoskeletal ultrasound (MSUS) as a complementary method to clinical assessment on rapid diagnosis and therapeutic decisions in a busy outpatient rheumatology clinic. Methods Sixty patients with different musculoskeletal symptoms were included in the study. Three expert rheumatologists performed the clinical examination and filled out a standardized clinical report sheet with the following parameters: general and/or local diagnoses, planned systemic and/or local treatment, and their decision concerning the use of MSUS evaluation complementary to clinical examination. Another rheumatologist, blinded to clinical data, performed the MSUS assessment of the anatomic areas selected by the clinicians. The impact of the new information obtained by MSUS on the initial diagnosis and therapeutic strategy was estimated by the degree of change in the initial clinical diagnosis and therapy decisions. Results Of 60 patients (67 anatomic areas), MSUS was considered as necessary after clinical examination in 39 patients (65%), totaling 43 anatomic areas (64.17%). An overall change of the initial clinical diagnosis was present in 60% of the anatomic areas (P = 0.0175). In all of the anatomic areas (100%), the new diagnosis was more objective and detailed. An overall change of the initial systemic therapy was present in 25% of anatomic areas (P = 0.0014) and in 36% of anatomic areas (P = 0.095) for local therapy. A guided diagnostic aspiration was decided to be performed in 15% of anatomic areas and a guided therapeutic injection in 22% of anatomic areas. Conclusion Enhanced information obtained by MSUS evaluation leads to changes, with a significant impact on the initial diagnosis and treatment strategy designed after clinical examination.